(untitled) (Experimental biology, 2015)
Application of phycocyanin at an anemia renders correction action on a structurally functional condition of biological membranes of rats, reducing activity of lipid peroxidation of membranes of the secretor cells of mammary gland of rats during the periods of mammo-and lactopoesis.